2021
DOI: 10.1177/0962280221990415
|View full text |Cite
|
Sign up to set email alerts
|

Sample size estimation for modified Poisson analysis of cluster randomized trials with a binary outcome

Abstract: The modified Poisson regression coupled with a robust sandwich variance has become a viable alternative to log-binomial regression for estimating the marginal relative risk in cluster randomized trials. However, a corresponding sample size formula for relative risk regression via the modified Poisson model is currently not available for cluster randomized trials. Through analytical derivations, we show that there is no loss of asymptotic efficiency for estimating the marginal relative risk via the modified Poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 54 publications
0
41
0
Order By: Relevance
“…It is possible to extend their approach to accommodate continuous co-primary endpoints as an alternative to our proposed method. However, previous work has shown that a GEE with an independence working correlation structure can result in an inflated sample size compared to an efficient GEE with correct working correlation model even with a single primary endpoint (Li and Tong, 2021). It would be interesting to formally quantify the efficiency gain by MLMM versus independence GEE with co-primary endpoints.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is possible to extend their approach to accommodate continuous co-primary endpoints as an alternative to our proposed method. However, previous work has shown that a GEE with an independence working correlation structure can result in an inflated sample size compared to an efficient GEE with correct working correlation model even with a single primary endpoint (Li and Tong, 2021). It would be interesting to formally quantify the efficiency gain by MLMM versus independence GEE with co-primary endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…, K) T , and specify the variance component matrices Σ φ and Σ e based on the marginal variances and ICCs. To further assess the accuracy of our approximate power procedure under unequal cluster sizes, we consider mean cluster size m = 60, and coefficient of variation of cluster size CV ∈ {0, 0.2, 0.4, 0.8}, representing different degrees of variability in cluster size used in previous simulations (Li and Tong, 2021). When CV > 0, the cluster sizes m i 's are drawn from a Gamma distribution with shape and scale parameter 1/CV 2 and mCV 2 ), rounded to the nearest integer.…”
Section: Simulation Studymentioning
confidence: 99%
See 2 more Smart Citations
“…which have been discussed in many papers [23] [24][25] [26] [27]. The log-binomial model uses the log link function for the binomial regression, while the modified Poisson regression applies the Poisson regression to binomial data and uses a robust error variance procedure known as the sandwich estimation to account for the model mis-specification.…”
Section: Introductionmentioning
confidence: 99%